SEJARAH DAN PROSES MASUKNYA ISLAM KE INDONESIA - Dea Rafika Syahputri; Mirna Yusmita; Dewi Ratna Sari; Sari Safira; Riana Safitri; Melinda Sari; Kamariah Kamariah; Rindiani Syahfitri; Eka Syahrani Salsabila; Suci Ramadhani; Intan Maulida; Dwi Intan Nabila; Darma Taksiah; Dinda Amaliana (JURNAL ILMIAH NUSANTARA, 2025)
Islam has significantly influenced the history and growth of civilization in Indonesia. The arrival of Islam in the archipelago was a key event in the nation's history. This is because Islam transformed not only religion but also politics, society, the economy, culture, and education. Islam came to Indonesia peacefully, slowly, and without coercion. This distinguishes it from the spread of other religions in other parts of the world. This qualitative research uses literature review methods to examine the history and how Islam arrived in Indonesia. Based on the researchers' findings, we can conclude that Islam entered Indonesia slowly, peacefully, and gradually. Traders, religious teachers, and local leaders spread the religion through social and cultural interactions.